The Influence of an Active Records Storage System and Motivation on Employee Performance with Competence as an Intervening Variable in Training Centers Medan Religion - Siti Aisyah Siregar; Kiki Farida Ferine (Lafadz Jaya Publisher, 2023)
The purpose of this study was to determine the effect of an active archive storage system and motivation on employee performance with competence as an intervening variable with an associative quantitative research type. This research was conducted at the Medan Religious Education and Training Center. The way to distribute questionnaires and the data source used is the primary data source. This research model uses an analysis tool and the measuring tool uses Smart PLS version 3.3.3. the results of this study are. Competence has no significant positive effect on employee performance. Motivation has no significant positive effect on employee performance. Motivation has no significant positive effect on competence. Active Archive Storage System has a positive and significant effect on Employee Performance. Active Archive Storage System has no significant positive effect on Competence. Motivation has no significant positive effect on Employee Performance through Competency of Active Archive Storage System has no significant positive effect on Employee Performance through Competence.